Aminocyclopropenium Ions: Synthesis, Properties, and Applications - Bandar, Jeffrey S.; Lambert, Tristan H. (Synthesis, 2013)
This review covers the preparation, physical properties, and applications of cyclopropenium ions bearing one, two, or three amino substituents. It provides a description of the most reliable methods to access these unique structures as well as a discussion of the reactivity profiles of the common subtypes.1 Introduction2 Preparation3 Properties3.1 Stability3.2 Redox Behavior3.3 Ion Pair Strain4 Reactions5 Applications5.1 Ionic Liquids5.2 Metal Complexes5.2.1 TDAC π-Complexes5.2.2 BDAC σ-Complexes5.2.3 Cyclopropenimine Ligands5.2.4 BDAC–Phosphorus Ligands5.3 Brønsted Bases6 Conclusion
Keywords: cyclopropenium ions; aromaticity; cyclopropenimines; ionic liquids; ligands